Statistical optimization of for chromium (IV) removal on aqueous solution using chitosan - Kabbashi, Nassereldeen Ahmed; Daoud, Jamal Ibrahim; Muyibi, Suleyman Aremu; Qudsieh, Isam Y. (INSI Publications, 2011)
In this work, a statistical model which can be used to evaluate the removal of chromium from aqueous solution using chitosan as an adsorbent has been developed. The experiment was described by varying chitosan dosage (10-30 mg), pH (5-8), contact time (10-90 min) and agitation speed (50-250 rpm). The initial chromium concentration was fixed to 20 mg/L. The results indicated that pH is the most significant factor that affects the removal of chromium. The R2 of 0.9963 showed that the overall model is good as the experimental values are close to predicted values. The optimized conditions obtained at 28.79 mg chitosan dosage, pH 6.39, 20.16 minutes contact time and agitation speed of 156.23 rpm. This optimum condition obtained to achieve 0.05 mg/L residual chromium concentration or 99.75% removal that meets DOE effluent discharge requirement.